RNA sequencing-based identification of the regulatory mechanism of microRNAs, transcription factors, and corresponding target genes involved in vascular dementia - Zhao, Kaiyue; Zeng, Li; Cai, Zhongdi; Liu, Mimin; Sun, Ting; Li, Zhuorong; Liu, Rui (Frontiers in Neuroscience, 2022)
Vascular dementia (VaD) is the second most common dementia with uncertain mechanisms and no effective treatments. microRNAs (miRNAs) and transcription factors (TFs), considered regulatory factors of genes, are involved in many diseases. Therefore, this work investigated the aberrantly expressed miRNAs, TFs, corresponding target genes, and their co-regulatory networks in the cortex of rats with bilateral common carotid artery occlusion (2VO) to uncover the potential mechanism and biomarkers of VaD. Differentially expressed genes (DEGs), miRNAs (DEMs), and TFs (DETFs) were identified using RNA sequencing, and their interaction networks were constructed using Cytoscape. The results showed that rats with 2VO had declined cognitive capabilities and neuronal loss in the cortex than sham rats. DEGs, DEMs, and DETFs were discriminated between rats with 2VO and sham rats in the cortex, as shown by 13 aberrantly expressed miRNAs, 805 mRNAs, and 63 TFs. The miRNA-TF-target gene network was constructed, showing 523 nodes and 7237 edges. Five miRNAs (miR-5132-5p, miR-764-3p, miR-223-3p, miR-145-5p, and miR-122-5p), ten TFs (Mxi1, Nfatc4, Rxrg, Zfp523, Foxj2, Nkx6-1, Klf4, Klf5, Csrnp1, and Prdm6), and seven target genes (Serpine1, Nedd4l, Pxn, Col1a1, Plec, Trip12, and Tpm1), were chosen as the significant nodes to construct feed-forward loops (FFLs). Gene Ontology and pathway enrichment analysis revealed that these miRNAs and TFs associated genes are mostly involved in the PI3K/Akt, neuroactive ligand-receptor interaction, calcium signaling, and Wnt signaling pathways, along with central locations around the cell membrane and organelles, exerting function such as growth factor binding, integrin binding, and extracellular matrix structural constituent, with representative biological processes like vasculature development, cell-substrate adhesion, cellular response to growth factor stimulus, and synaptic transmission. Furthermore, three miRNAs (miR-145-5p, miR-122-5p, and miR-5132-5p), six TFs (Csrnp1, Klf4, Nfatc4, Rxrg, Foxj2, and Klf5), and five mRNAs (Serpine1, Plec, Nedd4l, Trip12, and Tpm1), were confirmed by qRT-PCR as significantly changed in rats with VaD, in line with the alteration of RNA sequencing. miR-145-5p directly targeted Csrnp1 in their potential FFL. These results might help the understanding of the underlying regulatory mechanisms of miRNA-TF-genes in the pathogenesis of VaD, providing potential therapeutic targets.